The Impact of Promotion, Ease of Investment, and Gold Selling Value on the Profitability of Bank Syariah Indonesia Banyuwangi - Akhmad Syaifudin; Siti Masrohatin; Nikmatul Masruroh (The Eastasouth Journal of Social Science and Humanities, 2026)
The purpose of this study is to examine the impact of promotion, investment convenience, and gold selling value on the profitability of Bank Syariah Indonesia Banyuwangi. This research method uses a quantitative approach. The research sample consisted of 40 employees of Bank Syariah Banyuwangi, with sampling using the incidental sampling method. The research data used Multiple Regression Analysis with SPSS 27. The results showed that gold investment promotion has a negative and significant effect on the profitability of Bank Syariah Indonesia Banyuwangi, while investment convenience and gold selling value have a positive and significant effect on the profitability of Bank Syariah Indonesia Banyuwangi.